2007
DOI: 10.1002/ajmg.b.30504
|View full text |Cite
|
Sign up to set email alerts
|

Sustained attention and response inhibition in boys with fragile X syndrome: Measures of continuous performance

Abstract: Sustained attention and response inhibition were examined in boys with full mutation fragile X syndrome (FXS) using adapted visual and auditory continuous performance tests (CPTs). Only 61% of 56 boys with visual CPT data and 54% of 52 boys with auditory data were able to demonstrate sufficient understanding to complete the visual and auditory CPTs, respectively. Mental age (MA) predicted whether boys with FXS were able to demonstrate understanding of the CPTs. The performance of boys with FXS who were able to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
51
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(55 citation statements)
references
References 48 publications
3
51
0
1
Order By: Relevance
“…Furthermore, scientific research has revealed that already in infancy, those with FXS demonstrate poor response inhibition (Scerif, Cornish, Wilding, Driver, & Karmiloff-Smith, 2004, poor saccadic eye-movement control (Scerif, Karmiloff-Smith, Campos, Elsabbagh, Driver, & Cornish, 2005), and prolonged visual attention to objects or what is known as sticky fixation (Roberts, Hatton, Long, Anello, & Colombo, 2012). In subsequent FXS development, school children and adolescents also display poor response inhibition (Sullivan, Hatton, & Hammer, 2007) and atypical patterns of visual attention (Hooper, Hatton, & Baranek, 2000;Munir, Cornish, & Wilding, 2000a, 2000b. Finally, executive function is clearly deficient in FXS in childhood, with concomitant memory impairments (Lanfranchi, Cornoldi, & Drigo, 2009).…”
Section: Insights From Longitudinal Studies Of Fragile X 71 Cognitivementioning
confidence: 99%
“…Furthermore, scientific research has revealed that already in infancy, those with FXS demonstrate poor response inhibition (Scerif, Cornish, Wilding, Driver, & Karmiloff-Smith, 2004, poor saccadic eye-movement control (Scerif, Karmiloff-Smith, Campos, Elsabbagh, Driver, & Cornish, 2005), and prolonged visual attention to objects or what is known as sticky fixation (Roberts, Hatton, Long, Anello, & Colombo, 2012). In subsequent FXS development, school children and adolescents also display poor response inhibition (Sullivan, Hatton, & Hammer, 2007) and atypical patterns of visual attention (Hooper, Hatton, & Baranek, 2000;Munir, Cornish, & Wilding, 2000a, 2000b. Finally, executive function is clearly deficient in FXS in childhood, with concomitant memory impairments (Lanfranchi, Cornoldi, & Drigo, 2009).…”
Section: Insights From Longitudinal Studies Of Fragile X 71 Cognitivementioning
confidence: 99%
“…Los síntomas suelen aparecer a partir de los 2 años de edad, tienden a mejorar después de la pubertad y suelen ser los rasgos más importantes en niños con un funcionamiento elevado (inteligencia normal). En los casos de premutación pueden presentar síntomas de hiperactividad (Calvani et al, 2001;Sullivan et al, 2006;Sullivan et al, 2007;Beltrán et al, 2011).…”
Section: Déficit De Atención E Hiperactividadunclassified
“…Studies of FXS have shown particular deficits in sustained attention, response inhibition, working memory, and other executive functions associated with decisional capacity (Baker et al, 2011; Hooper et al, 2008; Ornstein et al, 2008; Sullivan et al, 2007). Reading is a challenge for males (Roberts et al, 2005); a national survey reported that although 44% of adult males with FXS could read basic picture books or simple stories, only 19% could read books that contain new words or concepts (Bailey, Raspa, Holiday, Bishop, & Olmsted, 2009).…”
Section: Fragile X Syndrome (Fxs)mentioning
confidence: 99%